2013
DOI: 10.1080/10410236.2013.816911
|View full text |Cite
|
Sign up to set email alerts
|

Lurking as an Active Participation Process: A Longitudinal Investigation of Engagement with an Online Cancer Support Group

Abstract: To better understand participation in computer-mediated social support (CMSS) groups for breast cancer patients, this study examines two overarching questions of: 1) who are posters, lurkers, or non-users? and 2) what role do these different types of engagement play in explaining psychosocial health outcomes? This study incorporates the comprehensive model of information seeking and two competing models of social enhancement and social compensation, as well as the literature of lurking and posting behaviors in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(76 citation statements)
references
References 49 publications
(101 reference statements)
2
73
0
1
Order By: Relevance
“…participant behaviours within the intervention and technology used to access the intervention) [9, 12]. For example, do active contributors show greater intervention effects than “lurkers” (those who view others’ posts but do not contribute original material themselves [21])? If so, researchers can work with designers and developers to refine the intervention to include persuasive cues that encourage participants’ active engagement with the intervention.…”
Section: How Can Paradata Analyses Advance the Field?mentioning
confidence: 99%
“…participant behaviours within the intervention and technology used to access the intervention) [9, 12]. For example, do active contributors show greater intervention effects than “lurkers” (those who view others’ posts but do not contribute original material themselves [21])? If so, researchers can work with designers and developers to refine the intervention to include persuasive cues that encourage participants’ active engagement with the intervention.…”
Section: How Can Paradata Analyses Advance the Field?mentioning
confidence: 99%
“…The magnitude of this social network platform and its popularity can considerably extend the reach of evidence-based health messages to the public and scale-up user-centered social support to the population level to address public health problems. In fact, a growing volume of research is leveraging social media to facilitate health behavior changes such as increasing physical activities [5], enabling addiction recovery support [6], providing support for cancer survivors [7,8], and reducing sexual risk behaviors among youth [9]. More evidence has shown that participants perceive social media approaches for health promotion as appealing, acceptable, and convenient [10].…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the level of engagement, cancer patients may participate in CMSS groups in a different manner (Han, Hou, Kim, & Gustafson, 2014). Since our findings suggest that cancer patients can empower themselves through productive communicative interaction with other patients, researchers and healthcare professionals should provide adequate communication trainings for patients so that they can communicate more effectively with such skills as initiating conversations, offering advice to other patients, and responding to other patients’ problems as they have experienced it.…”
Section: Discussionmentioning
confidence: 99%